Strategic communication and competitive advantage: Assessing CEO letters of global airline alliances - Gang-Hoon Seo; Munehiko Itō; Zhonghui Li (Foundations of Management, 2021)
For the last several decades, global airline alliances have ensured their market presence in the aviation industry. Scholars have focused on the effects of alliance affiliation for airlines and what the competitive advantages of alliances are. However, these issues have been discussed in relation to operational aspects. The quality of strategic communication can be an important factor in achieving a competitive advantage and realizing a differentiation strategy. This study assessed the differences in quality of strategic communication between the three leading alliance groups (oneworld, SkyTeam, and Star Alliance) and a non-alliance group. Comprehensive content analysis was implemented using the letters of chief executive officers (CEOs) of 46 airlines. We found that the non-alliance group has more ideal CEO letters than the alliance groups, and the main topics and quality of CEO letters of alliance group differed. This study provides a novel insight into the competitive advantage of global airline alliances.
Keywords: D74; L1; M16; M31; 650; global marketing strategy; strategic communication; competitive advantage; global airline alliance; CEO letter; CEO letter effectiveness